User Motivation and Barriers toward Library of Things at ITEBA - Tommy Andrea Gunawan; Dany Kurnia Gunawan; Zhilla Zhalila Qurrata A'yun; Jihan Nur Annisa (fakultas Desain Komunikasi Visual, 2026)
University libraries face significant challenges in engaging academic communities in the digital era. This pilot study investigates the motivations and barriers of the academic community at Institut Teknologi Batam (ITEBA) in utilizing library facilities, as an empirical foundation for Library of Things (LoT) implementation. A quantitative descriptive survey was administered to 51 respondents comprising students (74.5%), lecturers (13.7%), and non-academic staff (11.8%). Physical environment comfort (mean = 6.75/10) and conducive learning atmosphere (mean = 6.41/10) are the primary visit motivators, while the absence of engaging programs (43.1% agreement) and inflexible operating hours (37.3% agreement) are the main barriers. A total of 72.5% of respondents expressed strong interest in gamification-based reward programs. These findings provide a preliminary framework for designing a Library of Things platform at ITEBA that integrates non-book item lending with gamification mechanisms and user experience-centered digital service design.